mirror of
https://github.com/kalmarek/GroupRings.jl.git
synced 2024-11-19 06:30:27 +01:00
303 lines
9.0 KiB
Julia
303 lines
9.0 KiB
Julia
using Test
|
||
|
||
using AbstractAlgebra
|
||
using GroupRings
|
||
using SparseArrays
|
||
|
||
|
||
@testset "GroupRings" begin
|
||
@testset "Constructors: PermutationGroup" begin
|
||
G = PermutationGroup(3)
|
||
|
||
@test isa(GroupRing(G), AbstractAlgebra.Ring)
|
||
@test isa(GroupRing(G), GroupRing)
|
||
|
||
RG = GroupRing(G)
|
||
@test isdefined(RG, :basis) == true
|
||
@test length(RG.basis) == 6
|
||
@test isdefined(RG, :basis_dict) == true
|
||
@test isdefined(RG, :pm) == false
|
||
|
||
@test isa(GroupRing(PermutationGroup(6), rand(1:6, 6,6)), GroupRing)
|
||
|
||
RG = GroupRing(G, fastm=true)
|
||
@test isdefined(RG, :pm) == true
|
||
@test RG.pm == zeros(Int, (6,6))
|
||
|
||
@test isa(complete!(RG), GroupRing)
|
||
@test all(RG.pm .> 0)
|
||
@test RG.pm == GroupRings.fastm!(GroupRing(G, fastm=false), fill=true).pm
|
||
|
||
@test RG.basis_dict == GroupRings.reverse_dict(collect(G))
|
||
|
||
@test isa(GroupRing(G, collect(G)), GroupRing)
|
||
S = collect(G)
|
||
pm = create_pm(S)
|
||
@test isa(GroupRing(G, S), GroupRing)
|
||
@test isa(GroupRing(G, S, pm), GroupRing)
|
||
|
||
A = GroupRing(G, S)
|
||
B = GroupRing(G, S, pm)
|
||
|
||
@test RG == A
|
||
@test RG == B
|
||
end
|
||
|
||
@testset "GroupRing constructors FreeGroup" begin
|
||
using Groups
|
||
F = FreeGroup(3)
|
||
S = gens(F)
|
||
append!(S, [inv(s) for s in S])
|
||
|
||
basis, sizes = Groups.generate_balls(S, F(), radius=4)
|
||
d = GroupRings.reverse_dict(basis)
|
||
@test_throws KeyError create_pm(basis)
|
||
pm = create_pm(basis, d, sizes[2])
|
||
|
||
@test isa(GroupRing(F, basis, pm), GroupRing)
|
||
@test isa(GroupRing(F, basis, d, pm), GroupRing)
|
||
|
||
A = GroupRing(F, basis, pm)
|
||
B = GroupRing(F, basis, d, pm)
|
||
@test A == B
|
||
|
||
RF = GroupRing(F, basis, d, create_pm(basis, d, check=false))
|
||
nz1 = count(!iszero, RF.pm)
|
||
@test nz1 > 1000
|
||
|
||
GroupRings.complete!(RF)
|
||
nz2 = count(!iszero, RF.pm)
|
||
@test nz2 > nz1
|
||
@test nz2 == 45469
|
||
|
||
g = B()
|
||
s = S[2]
|
||
g[s] = 1
|
||
@test g == B(s)
|
||
@test g[s^2] == 0
|
||
@test_throws KeyError g[s^10]
|
||
end
|
||
|
||
@testset "GroupRingElems constructors/basic manipulation" begin
|
||
G = PermutationGroup(3)
|
||
RG = GroupRing(G, fastm=true)
|
||
a = rand(6)
|
||
@test isa(GroupRingElem(a, RG), GroupRingElem)
|
||
@test isa(RG(a), GroupRingElem)
|
||
|
||
@test all(isa(RG(g), GroupRingElem) for g in G)
|
||
|
||
@test_throws String GroupRingElem([1,2,3], RG)
|
||
@test isa(RG(G([2,3,1])), GroupRingElem)
|
||
p = G([2,3,1])
|
||
a = RG(p)
|
||
@test length(a) == 1
|
||
@test isa(a.coeffs, SparseVector)
|
||
|
||
@test a.coeffs[5] == 1
|
||
@test a[5] == 1
|
||
@test a[p] == 1
|
||
|
||
@test string(a) == "(1,2,3)"
|
||
@test string(-a) == " - 1(1,2,3)"
|
||
|
||
@test RG([0,0,0,0,1,0]) == a
|
||
|
||
s = G([1,2,3])
|
||
@test a[s] == 0
|
||
a[s] = 2
|
||
|
||
@test a.coeffs[1] == 2
|
||
@test a[1] == 2
|
||
@test a[s] == 2
|
||
|
||
@test string(a) == "2() + (1,2,3)"
|
||
@test string(-a) == " - 2() - 1(1,2,3)"
|
||
|
||
@test length(a) == 2
|
||
end
|
||
|
||
@testset "Arithmetic" begin
|
||
G = PermutationGroup(3)
|
||
RG = GroupRing(G, fastm=true)
|
||
a = RG(ones(Int, order(G)))
|
||
|
||
@testset "scalar operators" begin
|
||
|
||
@test isa(-a, GroupRingElem)
|
||
@test (-a).coeffs == -(a.coeffs)
|
||
|
||
@test isa(2*a, GroupRingElem)
|
||
@test eltype(2*a) == typeof(2)
|
||
@test (2*a).coeffs == 2 .*(a.coeffs)
|
||
|
||
ww = "Scalar and coeffs are in different rings! Promoting result to Float64"
|
||
|
||
@test isa(2.0*a, GroupRingElem)
|
||
@test_logs (:warn, ww) eltype(2.0*a) == typeof(2.0)
|
||
@test_logs (:warn, ww) (2.0*a).coeffs == 2.0.*(a.coeffs)
|
||
|
||
@test_logs (:warn, ww) (a/2).coeffs == a.coeffs./2
|
||
b = a/2
|
||
@test isa(b, GroupRingElem)
|
||
@test eltype(b) == typeof(1/2)
|
||
@test (b/2).coeffs == 0.25*(a.coeffs)
|
||
|
||
@test isa(convert(Rational{Int}, a), GroupRingElem)
|
||
@test eltype(convert(Rational{Int}, a)) == Rational{Int}
|
||
@test convert(Rational{Int}, a).coeffs ==
|
||
convert(Vector{Rational{Int}}, a.coeffs)
|
||
|
||
b = convert(Rational{Int}, a)
|
||
|
||
@test isa(b//4, GroupRingElem)
|
||
@test eltype(b//4) == Rational{Int}
|
||
|
||
@test isa(b//big(4), RingElem)
|
||
@test eltype(b//(big(4)//1)) == Rational{BigInt}
|
||
|
||
@test isa(a//1, GroupRingElem)
|
||
@test eltype(a//1) == Rational{Int}
|
||
@test (1.0a)//1 == (1.0a)
|
||
|
||
end
|
||
|
||
@testset "Additive structure" begin
|
||
@test RG(ones(Int, order(G))) == sum(RG(g) for g in G)
|
||
a = RG(ones(Int, order(G)))
|
||
b = sum((-1)^parity(g)*RG(g) for g in G)
|
||
@test 1/2*(a+b).coeffs == [1.0, 0.0, 1.0, 0.0, 1.0, 0.0]
|
||
|
||
a = RG(1) + RG(perm"(2,3)") + RG(perm"(1,2,3)")
|
||
b = RG(1) - RG(perm"(1,2)(3)") - RG(perm"(1,2,3)")
|
||
|
||
@test a - b == RG(perm"(2,3)") + RG(perm"(1,2)(3)") + 2RG(perm"(1,2,3)")
|
||
|
||
@test 1//2*2a == a
|
||
@test a + 2a == (3//1)*a
|
||
@test 2a - (1//1)*a == a
|
||
end
|
||
|
||
@testset "Multiplicative structure" begin
|
||
for g in G, h in G
|
||
a = RG(g)
|
||
b = RG(h)
|
||
@test a*b == RG(g*h)
|
||
@test (a+b)*(a+b) == a*a + a*b + b*a + b*b
|
||
end
|
||
|
||
for g in G
|
||
@test star(RG(g)) == RG(inv(g))
|
||
@test (one(RG)-RG(g))*star(one(RG)-RG(g)) ==
|
||
2*one(RG) - RG(g) - RG(inv(g))
|
||
@test aug((one(RG)-RG(g))) == 0
|
||
end
|
||
|
||
a = RG(1) + RG(perm"(2,3)") + RG(perm"(1,2,3)")
|
||
b = RG(1) - RG(perm"(1,2)(3)") - RG(perm"(1,2,3)")
|
||
|
||
@test a*b == mul!(a,a,b)
|
||
|
||
@test aug(a) == 3
|
||
@test aug(b) == -1
|
||
@test aug(a)*aug(b) == aug(a*b) == aug(b*a)
|
||
|
||
z = sum((one(RG)-RG(g))*star(one(RG)-RG(g)) for g in G)
|
||
@test aug(z) == 0
|
||
|
||
@test supp(z) == parent(z).basis
|
||
@test supp(RG(1) + RG(perm"(2,3)")) == [G(), perm"(2,3)"]
|
||
@test supp(a) == [perm"(3)", perm"(2,3)", perm"(1,2,3)"]
|
||
end
|
||
|
||
end
|
||
|
||
@testset "SumOfSquares in group rings" begin
|
||
∗ = star
|
||
|
||
G = FreeGroup(["g", "h", "k", "l"])
|
||
S = G.(G.gens)
|
||
S = [S; inv.(S)]
|
||
|
||
ID = G()
|
||
RADIUS=3
|
||
@time E_R, sizes = Groups.generate_balls(S, ID, radius=2*RADIUS);
|
||
@test sizes == [9, 65, 457, 3201, 22409, 156865]
|
||
E_rdict = GroupRings.reverse_dict(E_R)
|
||
pm = GroupRings.create_pm(E_R, E_rdict, sizes[RADIUS]; twisted=true);
|
||
RG = GroupRing(G, E_R, E_rdict, pm)
|
||
|
||
g = RG.basis[2]
|
||
h = RG.basis[3]
|
||
k = RG.basis[4]
|
||
l = RG.basis[5]
|
||
G = (1-RG(g))
|
||
@test G^2 == 2 - RG(g) - ∗(RG(g))
|
||
|
||
G = (1-RG(g))
|
||
H = (1-RG(h))
|
||
K = (1-RG(k))
|
||
L = (1-RG(l))
|
||
GH = (1-RG(g*h))
|
||
KL = (1-RG(k*l))
|
||
|
||
X = (2 - ∗(RG(g)) - RG(h))
|
||
Y = (2 - ∗(RG(g*h)) - RG(k))
|
||
|
||
@test -(2 - RG(g*h) - ∗(RG(g*h))) + 2G^2 + 2H^2 == X^2
|
||
@test (2 - RG(g*h) - ∗(RG(g*h))) == GH^2
|
||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 2GH^2 + 2K^2 == Y^2
|
||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) +
|
||
2(GH^2 - 2G^2 - 2H^2) +
|
||
4G^2 + 4H^2 + 2K^2 ==
|
||
Y^2
|
||
|
||
@test GH^2 - 2G^2 - 2H^2 == - X^2
|
||
@test -(2 - RG(g*h*k) - ∗(RG(g*h*k))) + 4G^2 + 4H^2 + 2K^2 == 2X^2 + Y^2
|
||
|
||
@test GH^2 == 2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2
|
||
@test KL^2 == 2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2*GH^2 + 2*KL^2 ==
|
||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2(2G^2 + 2H^2 - (2 - ∗(RG(g)) - RG(h))^2) +
|
||
2(2K^2 + 2L^2 - (2 - ∗(RG(k)) - RG(l))^2) ==
|
||
(2 - ∗(RG(g*h)) - RG(k*l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2(2G^2 + 2H^2) +
|
||
2(2K^2 + 2L^2) ==
|
||
(2 - ∗(RG(g*h)) - RG(k*l))^2 +
|
||
2(2 - ∗(RG(g)) - RG(h))^2 +
|
||
2(2 - ∗(RG(k)) - RG(l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2(2 - ∗(RG(g*h*k)) - RG(g*h*k)) + 2L^2 ==
|
||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||
|
||
@test 2 - ∗(RG(g*h*k)) - RG(g*h*k) ==
|
||
2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2(2GH^2 + 2K^2 - (2 - ∗(RG(g*h)) - RG(k))^2) + 2L^2 ==
|
||
(2 - ∗(RG(g*h*k)) - RG(l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2(2GH^2 + 2K^2) + 2L^2 ==
|
||
(2 - ∗(RG(g*h*k)) - RG(l))^2 +
|
||
2(2 - ∗(RG(g*h)) - RG(k))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
8G^2 + 8H^2 + 4K^2 + 2L^2 ==
|
||
(2 - ∗(RG(g*h*k)) - RG(l))^2 + 2(2 - ∗(RG(g*h)) - RG(k))^2 + 4(2 - ∗(RG(g)) - RG(h))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) +
|
||
2GH^2 + 2KL^2 == (2 - ∗(RG(g*h)) - RG(k*l))^2
|
||
|
||
@test -(2 - ∗(RG(g*h*k*l)) - RG(g*h*k*l)) + 2(2G^2 + 2H^2) + 2(2K^2 + 2L^2) ==
|
||
(2 - ∗(RG(g*h)) - RG(k*l))^2 + 2(2 - ∗(RG(k)) - RG(l))^2 + 2(2 - ∗(RG(g)) - RG(h))^2
|
||
end
|
||
end
|